A descriptive study on the efficacy and complications of the Capio (Boston Scientific) suturing device for sacrospinous ligament fixation. (22nd September 2017) - Mowat, Alex; Wong, Vivien; Goh, Judith; Krause, Hannah; Pelecanos, Anita; Higgs, Peta
Abstract : Background: Sacrospinous colpopexy is an effective vaginal apical support operation. Due to morbidity associated with traditional approaches which require wide dissection, slim‐line suture delivery devices have been introduced in the hope of reducing morbidity without compromise to outcomes. Aim: The aim of our series was to report outcomes and complications (particularly buttock pain and blood loss) of the sacrospinous colpopexy using the Capio suturing device and evaluate it against published results using the Miya hook. Methods: This is a prospective, multi‐centre descriptive study. The primary outcome is objective success at 12 months. Secondary outcomes include subjective success at 12 months, patient‐reported outcomes at 12 months, operating time, estimated blood loss and post‐operative buttock pain. Results: Fifty‐one consenting patients undergoing sacrospinous colpopexy were recruited at four Queensland hospitals. Objective success at 12 months was 95% (41/43) and subjective success at 12 months was 92% (44/48). Eighty‐four percent of patients reported buttock pain at one week, reducing to 16% by six weeks, of which 7% required analgesia. Conclusions: At a mean of 17 months follow up, we found that the sacrospinous colpopexy using the Capio suturing device provided excellent apical support with a low requirement for blood transfusion and an average operating time of seven minutes. We found a high rate of buttock pain immediately post‐operatively, but our rates became consistent with previous reports by six weeks post‐operation.